The Model of Appointing Judges of the Constitutional Court in a Constitutional Democracy - Prastiwi, Dian Eka; Yusdiansyah, Efik (PT FORMOSA CENDEKIA GLOBAL, 2024)
The very existence of the Constitutional Court is interpreted as a constitutional tribunal, which then becomes a new branch of power included in the judicial power. The model for appointing judges to the Constitutional Court may affect the independence and impartiality of the judiciary. In order to implement changes and improvements in the appointment of judges in Indonesia, we need to look at the model of appointment of constitutional judges in other countries. The aim of this research is to analyse the model of constitutional judges' appointment in Indonesia and compare it with the models of constitutional judges' appointment in other countries. The research method used is normative legal research by examining primary and secondary legal materials related to the appointment of constitutional judges. The research results show that there are several models of constitutional judge appointments in different countries, namely models involving the executive and legislative branches, models involving only the legislative branch, models involving all three branches of government, and models conducted by special institutions. Indonesia itself uses a model involving all three branches of government. This research also compares the system for appointing constitutional judges in Indonesia with other countries such as Germany, Austria and South Korea. The conclusion of this research is that the mechanism for appointing constitutional judges must be carried out in a transparent, independent and accountable manner in order to guarantee the independence of the Constitutional Court.